Phylogenetically more conservative epitopes among monoclonal antibody-defined antigenic sites of human transferrin are involved in receptor binding - Bártek, Jiří; Viklický, Vladimír; Stratil, Antonín (British journal of haematology, 1985)
Of eight monoclonal antibodies raised against human transferrin, one (H.TF-14) cross reacted with pig and rabbit transferrins and one (H.TF-1) showed cross-reactivity with horse and dog transferrins. While rabbit and pig transferrins exhibited the same patterns of binding to MOLT-3 cell receptors as human and horse transferrins, binding of mouse and dog transferrins was weaker and bovine and carp transferrins gave entirely negative results. The results of these competitive binding experiments were confirmed by a biological test in which bovine transferrin had no effect on the growth of MOLT-3 cells when added to a serum-free medium. The observed correlation between cross-reactivity of anti-transferrin monoclonal antibodies and the binding abilities of transferrins to the MOLT-3 cell receptors may be associated with the conservatism of the part of the transferrin molecule recognized by the cell receptor.
Keywords: Cattle; transferin; Animals; Epitopes; skot; Rabbits; kapři; ovce; Antibodies, Monoclonal; Binding, Competitive; receptory transferinu; lidé; zkřížené reakce; Transferrin; Dogs; koně; Cross Reactions; Receptors, Transferrin; Horses; Phylogeny; kompetitivní vazba; Sheep; receptory buněčného povrchu; Carps; Receptors, Cell Surface; monoklonální protilátky; králíci; epitopy; zvířata; fylogeneze; psi; Humans